The face mask: How a real protection becomes a psychological symbol during Covid-19? - Goh, Yihui; Tan, Benjamin Y.Q.; Bhartendu, Chandra; Ong, Jonathan J.Y.; Sharma, Vijay K. (Brain, behavior, and immunity, 2020)
•‘The Mask’ is the current byword and a precious possession.•For healthcare workers, wearing mask is a necessity for personal protection.•For general public, the mask is perhaps the most-powerful psychological symbol.•The mask undermines all other recommended practices of infection control measures.•We present evolution, types, filtration efficiency and recommended uses of mask. ‘The Mask’ has become a byword and a precious possession universally. Except for its use by the medical fraternity, answers to the common questions-whether it provides enough protection, which type is optimal for the general public and who really needs to don it, remain poorly understood. For a frontline healthcare worker, wearing mask is a necessity as an important person protection equipment, it is perhaps the most-powerful psychological symbol for the general public. Surprisingly, it even undermines all other recommended practices of infection control and breaking the transmission chain of Covid-19, like hand washing, personal hygiene and social distancing. ‘The mask’ has evolved with time and yet there is a need to further improve the design for safety, tolerability and comfort. In this review we present the journey of face mask, originating from the first masks aimed at stopping the bad smell to its industrial use to its all-important place in the medical field. Various types of face masks, their filtration efficiency, reusability and current recommendations for their use are presented.